Metal-free anti-biofouling coatings: the preparation of silicone-based nanostructured coatings via purely organic catalysis. Issue 2 (2nd April 2016) - Mincheva, Rosica; Beigbeder, Alexandre; Pettitt, Michala E.; Callow, Maureen E.; Callow, James A.; Dubois, Philippe
Abstract: The successful formulation of two-part condensation-curing silicone materials via purely organic catalysis is here developed and investigated as fouling-release coating. Several non-toxic organic catalysts and their 'onium' salts were studied as potential purely organic catalysts on the silicone condensation reaction but also on the properties of the resulting cured resins. The trifluoroacetic acid was pointed suitable for the production of condensation-curing silicone coatings. To assess favorable fouling-release properties, multi-wall carbon nanotubes (0.05–0.2 wt-%) were added to the resin. Interestingly, the catalytic activity of the trifluoroacetic acid proved not affected by the presence of the nanocharge. The properties of the coatings prepared using 0.1 wt-% acid revealed constant degree of crosslinking independently of the carbon nanotubes loading and pronounced surface nanostructuring suitable for fouling release. This final property was tested against Ulva linza sporelings and revealed that the coatings are highly suitable for fouling-release applications. Graphical abstract: